2022
DOI: 10.1111/acer.14932
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double‐blind, placebo‐controlled, pharmacogenetic study of ondansetron for treating alcohol use disorder

Abstract: Background: In a previous study, ondansetron, a serotonin 5-HT 3 receptor antagonist, reduced drinking intensity (drinks/drinking day [DPDD]) among European-ancestry (EA) participants with moderate-to-severe alcohol use disorder (AUD) and variants in genes encoding the serotonin transporter (SLC6A4) and 5-HT 3A (HTR3A), and 5-HT 3B (HTR3B) receptors. We tested whether (1) ondansetron reduces DPDD among individuals of either European or African ancestry (AA), and (2) that reductions in DPDD are greatest among o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…These positive observations replicated our previous ndings (Phase 2a clinical study) wherein low-dose ondansetron was shown to be e cacious at reducing various markers of alcohol consumption in early-onset (but not late-onset) AUD 27 , and among the same speci c genotypes 38 . Other studies have found similar directional results 24,27,34,35,38 except for a recent study 51 , which may have failed because of insu cient statistical power, failure to choose the correct drinking characteristic endophenotype, and the nonstandardized use of the psychosocial intervention (BBCET), with a possible related in ation of the placebo response (Johnson BA, Addolorato G, Lesch O, Liu L, Rodd ZA. A critical scienti c evaluation of a purportedly negative data report -response to…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These positive observations replicated our previous ndings (Phase 2a clinical study) wherein low-dose ondansetron was shown to be e cacious at reducing various markers of alcohol consumption in early-onset (but not late-onset) AUD 27 , and among the same speci c genotypes 38 . Other studies have found similar directional results 24,27,34,35,38 except for a recent study 51 , which may have failed because of insu cient statistical power, failure to choose the correct drinking characteristic endophenotype, and the nonstandardized use of the psychosocial intervention (BBCET), with a possible related in ation of the placebo response (Johnson BA, Addolorato G, Lesch O, Liu L, Rodd ZA. A critical scienti c evaluation of a purportedly negative data report -response to…”
Section: Discussionmentioning
confidence: 88%
“…Combining the strati cation of subjects by level of alcohol consumption and genotype results in speci c essential factors. We have learned that studying for genetic markers within subgroups requires a study of ample sample size, a criterion if not ful lled can lead to equivocal or possibly false-negative results 51 . We feel that this report is a veri cation of the need to have proper statistical power (sample size) to conduct accurate precision medicine clinical research.…”
Section: General Proceduresmentioning
confidence: 99%
“…A 16-week RCT (N = 95 individuals with AUD, including 58 of European and 37 of African ancestry) sought to replicate and extend these findings (Seneviratne et al, 2022) by comparing low-dose ondansetron (0.33 mg twice daily) or placebo. To assess pharmacogenetic effects, the sample was stratified into "responsive" and "nonresponsive" genotype groups using population-specific variation at genes encoding the serotonin transporter and the serotonin-3A and serotonin-3B receptors.…”
Section: Pharmacogenetics Of Baclofenmentioning
confidence: 99%
“…Combining the strati cation of subjects by level of alcohol consumption and genotype results in speci c essential factors. We have learned that studying for genetic markers within subgroups requires a study of ample sample size, a criterion that which not ful lled can lead to equivocal or possibly false negative results 57 . We feel that this report is a veri cation of the need to have proper statistical power (sample size) to conduct accurate precision medicine clinical research.…”
Section: General Proceduresmentioning
confidence: 99%